Core of the yoga sutras the definitive guide to the philosophy of yoga - Iyengar, B. K. S. 1918-2014 Bellur Krishnamachar Sundararaja Iyengar (London HarperThorsons, 2012)
A study of the philosophical core of yoga offers commentary on and explanations of Patañjali's sutras and illuminates the spirituality that is the foundation of yoga practice, in a work containing the sutras in their original language.
Includes index.
Keywords: Yoga -- Philosophy; Patañjali.; Philosophy—History.; Theology, Doctrinal